The Figure of Omid Safi: Progressive Muslim, Gender Mainstreaming, and Islamic Education - Rohinah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This study aims to determine Omid Safi's concept in the current discourse on gender equality and Islamic education. This study uses qualitative methods with critical and philosophical literal studies. It develops methods by collecting related literature, highlights essential concepts, categorizes information, applies similar procedures to other texts, extracts some concepts, and finds other supporting information. The results show that progressive Muslims are the central theme of Omid Safi's concept. Progressive Muslims study textual sources and materials in the Islamic tradition, interpret them and then link the ancient traditions with the contemporary era. Safi calls them as multiple critiques. Safi, in his concept on progressive Muslims, presents writings that offer an agenda of gender equality. It emphasizes a new paradigm of interpretations of the Qur'an and Hadith, which are considered imperfect because they are still based on the interests of particular groups so that the position of women is always marginalized. People's understanding that is still partial to the distinction between feminism and gender is also the cause of gender injustice. Women in their historical trajectory have proven their success in playing a heavier social role than men. Furthermore, Safi's concept in education, especially Islamic education, has a primary focus on the "teacher figure" as a prototype for Muslims who must have a progressive perspective and paradigm. This study highlights and interprets Omid Safi's concept of progressive Muslims in the discourse of gender and Islamic education.